MEDIA AND TECHNOLOGY AS RADICAL SOLUTIONS IN OVERCOMING THE EDUCATION CRISIS DURING THE PANDEMIC: MEDIA AND TECHNOLOGY AS RADICAL SOLUTIONS IN OVERCOMING THE EDUCATION CRISIS DURING THE PANDEMIC (PENDAIS, 2024)
The spread of the COVID-19 virus/outbreak that has hit all countries in the world, including Indonesia, began to be felt since 2020. The implementation of national education is reflected in the applicable curriculum because the curriculum in education has its position as a guideline for the implementation of education as well as an instrument to achieve the goals of national education. The implementation of distance education or online learning is at least the right solution in conducting learning in the pandemic. Considering that even though the country is in a state of emergency, education is not stopped because education is dynamic according to the times. With this solution, it can also guarantee citizens, especially school-age children, to get education as a citizen's right.The author in processing research data through several procedures, starting with data collection, then reducing data, Then display the data and the last step is to verify the data.Learning using networks is content and media provided to operationalize the implementation of education during a pandemic, has challenges and also hopes for the world of education. The challenges faced are related to the geographical location of Indonesia's territory as an archipelagic and maritime country so that not all regions can have internet networks including light networks evenly.